DIGITALISASI LAYANAN KOPERASI SAWIT BERBASIS WEB-MOBILE: STUDI PKM DI KOPERASI JAYA SEMPURNA, PALI - Usman Ependi; Sabeli Aliya; Dedi Irawan (Universitas Mataram, 2025)
The main issues faced by the target partner are the limited access to technical information regarding oil palm cultivation and the inefficiency of manual data management in the cooperative. To address these issues, the program proposes a solution in the form of the development of the Agrisawit application (for farmers) and the Cooperative Dashboard (for cooperative managers), both web and mobile-based, which is expected to facilitate farmers in accessing information related to oil palm cultivation, as well as making it easier for cooperative managers to manage data and communicate with members. The main objective of this community service program is to improve the operational efficiency and productivity of oil palm farmers at Koperasi Jaya Sempurna, Desa Pengabuan, Kecamatan Abab, Kabupaten PALI, South Sumatra Province, through the implementation of a digital-based information system. The program also includes digital literacy training for cooperative managers and members. Evaluation results show an 80% increase in application usage, a productivity increase in oil palm ranging from 45-90%, and a 90% improvement in the operational efficiency of the cooperative. This program is expected to have a sustainable positive impact on the cooperative and its members, and to serve as a model for the development of technology-based agribusiness in rural areas.